Extinction risk or lack of sampling in a threatened species: Genetic structure and environmental suitability of the neotropical frog Pristimantis penelopus (Anura: Craugastoridae) - Restrepo, Adriana; Velasco, Julian A.; Daza, Juan M. (Papéis Avulsos de Zoologia, 2017)
IUCN Red Lists have been a valuable tool to prioritize conservation plans in endemic neotropical frogs. However, many areas in this region are poorly known in terms of their diversity and endemism. Based on examined museum specimens of the threatened species Pristimantis penelopus we revised its geographic distribution and determined the habitat suitability using niche modeling techniques. Using a mitochondrial fragment of COI gene, we determine the phylogenetic position and the extent of the genetic variation across its distribution in Colombia. We present the first records of P. penelopus for the Cordillera Oriental, the western versant of Cordillera Occidental and the northern portion of the Cauca river basin. Based on the molecular phylogenetic analysis, Pristimantis penelopus belongs to the P. ridens series sensu Padial et al. (2014). The mean of intraspecific genetic variation is 2.1% and the variation among population ranges between 2.3 and 3.5%. The genetic distance between the western populations and the Magdalena Valley populations suggests a potential phylogeographic break in northwestern Antioquia. We expand the realized distribution by 258 kilometers north, 200 km east and 223 km northwest. Based on our results and according to the IUCN criteria we propose a new category for the species and highlight the need to increase the surveys in poorly known regions to better understand the geographic distribution and conservation status of listed species.